2016
DOI: 10.5152/turkpediatriars.2016.3566
|View full text |Cite
|
Sign up to set email alerts
|

Celiac disease in children and adolescents with Hashimoto Thyroiditis

Abstract: Aim: The aim of this study was to evaluate clinical and laboratory findings and determine the prevalence of celiac disease (CD) in children with Hashimoto thyroiditis (HT). Material and Methods:The data of a total of 80 patients with positive anti-thyroid antibodies who were aged between 6 and 17.9 years were retrospectively studied. Age, gender, complaints at the time of presentation, family history of thyroid disorders, clinical and laboratory findings were recorded. The levels of thyrotropin, free thyroxin,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
2
16
0
Order By: Relevance
“…Out of 56 studies included in the systematic review, 25 were case‐control studies, 24‐47 17 were cohort studies 48‐64 and 14 were cross‐sectional studies 65‐78 . No clinical trials met the criteria used in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…Out of 56 studies included in the systematic review, 25 were case‐control studies, 24‐47 17 were cohort studies 48‐64 and 14 were cross‐sectional studies 65‐78 . No clinical trials met the criteria used in the systematic review.…”
Section: Resultsmentioning
confidence: 99%
“…The results of many studies evidenced an association between Hashimoto's thyroiditis and coeliac disease or an asymptomatic increase in anti-tissue transglutaminase antibodies [5][6][7][8]. Autoimmune thyroiditis is the most prevalent coexisting autoimmune disorder in patients with celiac disease [9].…”
Section: Article Thiemementioning
confidence: 99%
“…Euthyroidism is the most common thyroid pattern associated with Hashimoto's thyroiditis (20-80%). Dundar et al (13) reported euthyroidism in 62.8% of children and adolescents with Hashimoto's thyroiditis, Özen et al (14) and Tuhan et al (15) reported euthyroidism in 51.2% and 36.7% of these cases, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…It has been reported that thyroid functions in children with Hashimoto's thyroiditis are mainly associated with the age of the cases and the possibility of subclinical and overt hypothyroidism increases with age (9) . Contrarily, it has been reported in the literature that patients with thyroid dysfunction are younger, and this condition has been explained with the view that early onset HT could have a worse prognosis (1,15,16) . However, in our study, no significant difference was found between age and thyroid functions which may be due to the small number of cases in our study population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation